RELIGIUSITAS SEBAGAI TERAPI UNTUK MEREDUKSI POTENSI AGRESI KRIMINALITAS PADA TINDAKAN OKNUM APARAT KEAMANAN - FX Wahyu Widiantoro, Nurhadi, & Andri Azis Putra (Jurnal Psikologi, 2017)
Objectives of this study were 1) explaining criminal aggression potency, 2) exploring thepossibilities of religiosity therapy to lessen the aggression potency. This research involved 3policemen in Yogyakarta since they had predisposition to act aggressively when opposing acriminal suspect. This was a descriptive qualitative research. This research revealed that therewere either internal or external factors underlying the aggressive behavior, especially whenthey were opposing criminal suspect. The internal factor was the low level of self-regulation.The external factor related with work environment such as huge assignments from theirseniors. At the discussion, it was provided a training explanation for policemen to lessen theirpredisposition to act aggressively.Key words: Criminal aggression, religiosity, policeman.